Peningkatan Kemampuan Guru Dalam Menyusun Modul Pembelajaran Berbasis Aktivitas Melalui Kegiatan Pendampingan di SD Muhammadiyah Sapen Yogyakarta - Wuri Wuryandani; Ratna Hidayah; Agung Rahmanto (DEDIKASI: Community Service Reports, 2022)
Utilizing learning materials that meet the requirements with the content of activities in learning activities is a form of teacher's efforts to create learning that actively develops student development. One form of teaching material that teachers can use is an activity-based learning module. The mentoring activity for the preparation of activity-based learning modules aims to improve the ability of teachers to develop activity-based modules as mentoring teaching materials for students at SD Muhammadiyah Sapen Yogyakarta. The number of teachers who participated in this activity was 92 teachers. Activities are carried out through several stages, namely activity-based learning module workshops, assistance in the preparation of activity-based learning modules, and evaluation of the results of activity-based learning module preparation. Based on the data obtained after participating in mentoring activities, they are in an outstanding category, where as many as 122 activity-based learning modules are declared feasible. The learning modules prepared by the teachers have been implemented in learning activities for the odd and even semesters of the 2021/2022 school year.